Analysis of Teacher Problems in Implementing The Kurikulum Merdeka in The Learning Process - Purbadianti, Novela Hayunda; Ahdhianto, Erif; Barus, Yohannes Kurniawan (Proceedings Series of Educational Studies, 2024)
Curriculum changes often give rise to new challenges. Therefore, in changing this curriculum, schools as implementers of the educational process are required to have a deeper understanding of the content and objectives of the new curriculum. The aim of this research is to determine: (1) the implementation of the Kurikulum Merdeka; (2) obstacles faced by teachers in implementing the Kurikulum Merdeka; (3) teacher efforts to overcome problems related to the implementation of the Kurikulum Merdeka. Researchers used a qualitative descriptive methodology. The data collection process uses techniques such as observation, interviews and documentation. The results of this research are: (1) The Merdeka Curriculum has been implemented at SDN 1 Gador for approximately two years in stages; (2) Teachers experience difficulties in making learning plans, choosing teaching methods and strategies that are appropriate for students, and designing assessment and evaluation instruments when implementing the Kurikulum Merdeka; (3) To overcome these problems, teachers use strategies such as discussing difficulties in KKG forums, making reflection journals, and making class agreements. Keywords: teacher; problems ; curriculum